Potential Therapeutic Agents Against Par-4 Target for Cancer Treatment: Where Are We Going? - Santos, Renata Virgínia Cavalcanti; de Sena, Wanessa L. B.; dos Santos, Flaviana A.; da Silva Filho, Antônio Felix; da Rocha Pitta, Marina Galdino; da Rocha Pitta, Maira Galdino; de Melo Rego, Moacyr Barreto; Pereira, Michelly Cristiny (Current Drug Targets, 2019)
One of the greatest challenges of cancer therapeutics nowadays is to find selective targets successfully. Prostate apoptosis response-4 (Par-4) is a selective tumor suppressor protein with an interesting therapeutic potential due to its specificity on inducing apoptosis in cancer cells. Par-4 activity and levels can be downregulated in several tumors and cancer cell types, indicating poor prognosis and treatment resistance. Efforts to increase Par-4 expression levels have been studied, including its use as a therapeutic protein by transfection with adenoviral vectors or plasmids. However, gene therapy is very complex and still presents many hurdles to be overcome. We decided to review molecules and drugs with the capacity to upregulate Par-4 and, thereby, be an alternative to reach this druggable target. In addition, Par-4 localization and function are reviewed in some cancers, clarifying how it can be used as a therapeutic target.
Keywords: therapeutic protein